Synthesis, spectral characterization and bioactivity evaluation of novel α-aminophosphonates. (4th March 2017) - Subramanyam, Ch.; Thaslim Basha, Sk.; Madhava, G.; Nayab Rasool, Sk.; Adam, Sk.; Durga Srinivasa Murthy, S.; Naga Raju, C.
GRAPHICAL ABSTRACT: ABSTRACT: A facile synthesis of novel α-aminophosphonates5a-j was accomplished by condensation of imines (3a-j) with diethyl phosphite (4 ) in ethanol at 50–60°C using easily recoverable and reusable catalyst, tetramethyl guanidine (TMG) via pudovik reaction in high yields. All the title compounds were characterized by spectral and elemental analysis. They were further screened for their abilities towards in vitro antibacterial, antifungal and antioxidant activities. The compounds5g, 5d, 5f exhibited good antibacterial and antifungal activities compared to the standard bactericide, Penicillin and fungicide, Griseofulvin, respectively. The compounds5h, 5i, 5g, and5c exhibited good antioxidant activity compared to the standard ascorbic acid.